Commentary: Urban Arts Pedagogy at James Lyng High School (LEARNing Landscapes, 2016)
Melissa Proietti is a PhD student at McGill University as well as a youth worker and street art coordinator at James Lyng High School in Montreal. In this interview, she describes an urban arts pedagogy project at the school. In its rst year, the students, in collaboration with McGill and various community groups, created a gallery space in the school and held their rst exhibit. Ms Proietti talks about the advantages of incorporating urban arts in the school curriculum and the lessons she learned from working with students on the project.
Keywords: urban art; pedagogy; interview; school; curriculum